Sequences and Series
      Geometric sequence/progression
         General term of a geometric sequence
      The sum of the first n terms of a finite geometric sequence, geometric series
          Geometric sequences, examples
Geometric sequence or progression
A sequence of numbers in which the ratio r of each two successive terms an / an -1 is constant or whose each term is r times the preceding.
For example, in the sequence 1, 3, 9, 27, . . . ,  each term is 3 times the preceding, that is r = 3.
Therefore, a geometric sequence can be written as
a1a2a3a4, . . . , an -1an, . . .    or    a1a1 ra1 r2a1 r3, . . . , an -1an, . . . 
where,    a2 = a1 r,
             a3 = a1 r2,
             a4 = a1 r3, and so on.
So, the formula for the nth term, or the general term of a geometric sequence is
  an = a1 rn -1.  
A geometric sequence is said to be convergent if   -1 < r < 1 that is, an approaches zero as n becomes infinitely large thus, the limit of the sequence is 0. 
An infinite sequence that has no a finite limit is called a divergent sequence.
The sum of the first n terms of a finite geometric sequence, geometric series
The sum of numbers in a geometric sequence we call the geometric series and write,
                             Sn = a1 + a2 + a3 + . . . + an -1 + an,
           that is         Sn = a1 + a1 r + a1 r2 + . . . + a1 rn -2 + a1 rn -1,
                 or         Sn = a1 (1 + r + r2 + . . . +  rn -2 + rn -1)
thus,      the sum of the first n terms of a finite geometric sequence or series.
Recall that by factoring binomial   xn - yn = (x - y) (xn -1 + xn -2y + xn -3y2 + . . . + xyn -2 + y n -1)
                                  so that,    rn - 1n = (r - 1) (rn -1 + rn -2 + rn -3 + . . . + r2 + r + 1).
Or, we can use following method to derive the same formula,
                             Sn = a1 + a1 r + a1 r2 + . . . + a1 rn -2 + a1 rn -1,
       and           r   Sn = a1 r + a1 r2 + a1 r3 + . . . + a1 rn -1 + a1 rn,
      then    r Sn - Sn = a1 rn - a1   or    Sn (r - 1) = a1 (rn - 1)  =>   Sn = a1 (rn - 1) / (r - 1).
Geometric sequences, examples
Example:  Find the sum of the first six terms of the geometric sequence 1, 3, 9, 27, 81, 243, 729, . . . 
Solution:   Since,   a1 = 1,  r = 3  and  n = 6
we plug these values into the formula for the first n terms of a finite geometric sequence,
Sn = [a1 (rn - 1)] / (r - 1) = [1 (36 - 1)] / (3 - 1) = 728 / 2 = 364.
Example:  Find the first term a1 and the number of terms n in a geometric sequence with the general term an = 192, the sum of the first n terms Sn = 381 and the common ratio r = 2.
Solution:  Using the formulas for an and Sn we get the system of two equations in two unknown,
Therefore, the geometric sequence is  3, 6, 12, 24, 48, 96, 192 . . . 
Example:  Write the geometric sequence such that the sum of its first three terms is 21 and the difference between the first and the second term is 12. 
Solution:  Given are the equations,
          (1)  a1 + a2 + a3 = 21      or       a1 + a1r + a1r2 = 21,          a1 (1 + r + r2) = 21
 and    (2)  a1 - a2 = 12                        a1 - a1r = 12,                    a1 (1 - r) = 12   
Thus, the two geometric sequences satisfy the given conditions,
              (a1)1 = 3    and   r1 = -3    give    3, -9, 27
              (a1)2 = 16  and   r2 = 1/4   give   16, 4, 1.
College algebra contents G
Copyright 2004 - 2020, Nabla Ltd.  All rights reserved.